Synthesis, Crystal Structure, Luminescence, and Nonlinear Optical Properties of 2-[(E)-[[4-[2-(4-Methoxyphenyl)ethynyl]phenyl] imino]methyl]-4-[(E)-phenyldiazenyl]phenol - Mohite, Sagar S.; Patil-Deshmukh, Aditya Babasaheb; Chavan, Sanjay Shamrao (Letters in Organic Chemistry, 2020)
2-((E)-((4-((4-methoxyphenyl)ethynyl)phenyl)imino)methyl-4-((E)phenyldiazenyl)phenol (1) have been synthesized and characterized. X-ray single crystal diffraction study of the compound 1 reveal a monoclinic structure. Room temperature luminescence is observed for 1 in CH2Cl2 solution due to π* → π transition. The SHG efficiency by Kurtz powder technique indicating the compound 1 displayed the second harmonic generation (SHG) property.
Keywords: NMR spectra